Identification and characterization of endophytic bacteria isolated from root nodules of lentil (Lens culinaris L.) grown on saline soils - Jabborova, D.; Bozorov, T.; Li, L.; Kistaubayeva, A.; Egamberdieva, D. (International Journal of Biology and Chemistry, 2021)
In this study the endophytic bacteria from root nodules of lentil (Lens culinaris L.) grown on saline soils were isolated and their beneficial properties for plants were characterized. A total of 12 isolates were isolated from nodules and four isolates (L2, L6, L9, L10) were able to produce lipase, protease and cellulose enzymes. All bacterial isolates were positive to glucanase activity. Eleven isolates did not show antagonistic activity against fungal strains Fusarium (F.) oxysporum, F. equiseti and Verticillium (V.) dahliae. One isolate (L10) appeared to have the highest antifungal activity against F. oxysporum, F. equiset and V. dahlia. The effect of bacterial isolates of plant growth promoting rhizobacteria (PGPR) on root and shoot growth of lentils were studied in pot experiments. The result revealed that among twelve isolates only five bacteria (L2, L4, L5, L9 and L10) increased significantly the fresh weight of lentil. The 16S rRNA sequencing data showed that five bacterial isolates, which showed the positive effect on plant growth, belong to Bacillus (B.) subtilis L2, Rhizobium sp. L4, Enterobacter tabaci L4, B. cereus L9, and B. velezensis L10. They can possibly be suggested as microbial inoculants for lentil under saline soil conditions. Among bacterial isolates B. velezensis L10 could be used as a biological control agent to protect lentil from fungal pathogens.